Political Marketing-Based Political Communication Strategy in the 2024 Bandung City Election: A Case Study of Muhammad Farhan And Erwin's Winnings - Sarah Pamela (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study analyzes the political communication strategies implemented by the Muhammad Farhan and Erwin ticket in the 2024 Bandung City Regional Election using a political marketing perspective. In the context of modern electoral democracy, political communication is no longer understood solely as a campaign activity, but rather as a strategic process that is voter-centered and designed to respond to public needs and preferences. This study uses a qualitative approach with a case study method, with data collection techniques through document analysis, literature review, and secondary data collection sourced from mass media, social media, electability survey results, and official publications of related institutions. The results show that the success of the Farhan-Erwin ticket is influenced by the implementation of an integrated political marketing strategy, including the use of social media as the main arena for political communication, the use of political branding through the slogan